Effect of aluminisation characteristics on the microstructure of single phase β-(Ni, Pt)Al coating and the isothermal oxidation behaviour. (May 2016) - Yang, Y.F.; Jiang, C.Y.; Bao, Z.B.; Zhu, S.L.; Wang, F.H.
Graphical abstract: The schematic illustration shows the effect of aluminising temperature and time on the thickness of final β-(Ni, Pt)Al coating when initial Pt plating was 5 μm. Either increasing temperature or extending duration can enhance the coating thickness, but the most efficient way is to increase them at the same time. Highlights: Single phase β-(Ni, Pt)Al coating was prepared by 'above-pack' aluminisation. Linear relationships were observed between coating thickness and aluminising characteristics. An empirical equation was proposed to predict the coating thickness with satisfying fitness. Better oxidation resistance was confirmed on the β-(Ni, Pt)Al coating with 5 μm Pt. There exists an optimal Pt content in β-(Ni, Pt)Al coating with improved oxidation resistance. Abstract: In the present study, single phase β-(Ni, Pt)Al coatings were prepared in sequence of Pt electroplating and 'above pack' aluminisation treatments. Three chief processing factors, including initial Pt thickness, aluminising temperature and time, were selected to investigate their influences on the microstructure of final β-(Ni, Pt)Al coating. Isothermal oxidation behaviour of the coatings with different thickness of Pt was evaluated at 1100 °C in static air. An empirical equation was proposed to show relationship between coating thickness and the three processing parameters. The β-(Ni, Pt)Al coating of 5 μm Pt showed the best oxidation resistance due to superior adhesion of oxide scale.